Evaluation of Emerging Antimicrobials Resistance in Nosocomial Infections Caused by E. coli: The Comparison Results of Observed Cases and Compartmental Model - Babak Eshrati; Elaheh Karimzadeh-Soureshjani; Mahshid Nasehi; Leila Janani; Hamid Reza Baradaran; Saeid Bitaraf; Pouria Ahmadi Simab; Sara Mobarak; Sasan Ghorbani Kalkhajeh; Mohammad Kogani (Interdisciplinary Perspectives on Infectious Diseases, 2025)
Conclusion: This study demonstrated the utility of the compartmental model in forecasting outbreaks of antibiotic-resistant E. coli. It provides a framework for investigating similar outbreaks in the future, using diverse data sources and methodologies.